Atroposelective Synthesis of Biaryl Diamines and Amino Alcohols via Chiral Phosphoric Acid Catalyzed para-Aminations of Anilines and Phenols - Wang, Donglei (iScience, 2019)
A versatile method for atroposelective synthesis of chiral biaryl diamines and amino alcohols has been developed via para-amination of anilines and phenols with azodicarboxylates enabled by chiral phosphoric acid catalysis. Meanwhile, highly efficient kinetic resolution of the racemic biaryl anilines has also been realized through these reactions, giving selectivity factor up to 246. The gram-scale reaction and facile derivatizations of the chiral products well demonstrate the potential of these reactions in the development of novel chiral ligands and catalysts.